1972
DOI: 10.1177/00220345720510030601
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Studies of Caries-Free and Caries-Active Students : I. Prevalence of Potentially Cariogenic Streptococci

Abstract: No significant difference was found in the prevalence of four potentially cariogenic streptococcal serotypes on molar surfaces of caries-free and caries-active students. Presence alone of these organisms did not correlate with the caries status of the individual. Other supplementary factors, apparently, are necessary for the induction of caries. Quantitative microbiologic procedures are needed to establish a more definitive elucidation of the role of specific microbiota in human dental caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…It is noteworthy that types a and b S. mutans were not found in our clinical isolates. Previous reports by Bratthall [3] and Duany et al [9] showed that types a and b S. mutans were most prevalent in the subjects with permanent dentition in Miami and Cairo, respectively. The study of Grenier et al [19] revealed that all plaque samples obtained from 14 to 16-year-old boys in Michigan, U.S.A., contained organisms which gave a specific reaction with anti-a and d antisera, and type b S. mutans was present in 74% of the plaque samples.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that types a and b S. mutans were not found in our clinical isolates. Previous reports by Bratthall [3] and Duany et al [9] showed that types a and b S. mutans were most prevalent in the subjects with permanent dentition in Miami and Cairo, respectively. The study of Grenier et al [19] revealed that all plaque samples obtained from 14 to 16-year-old boys in Michigan, U.S.A., contained organisms which gave a specific reaction with anti-a and d antisera, and type b S. mutans was present in 74% of the plaque samples.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these organisms comprise a distinct subgroup of the viridans streptococci (15), which we refer to as the mutans streptococci. All mutans streptococci which have been tested in appropriate animal model systems can induce dental caries of varying degrees of severity (16,19,20,22,33,37,53), and they are considered to be a major factor in the etiology of human dental caries (4, 13,14,22,24,27,31,40).…”
mentioning
confidence: 99%
“…The results indicate that serotype c of S. mutans, the predominant serotype found in the oral cavity and the serotype with the greatest propensity for colonisa tion [4,13], has a unique capacity to suppress PMN activation not shown by other serotypes. These find ings may have biological relevance, as successful bac terial colonisation of the oral cavity would depend in part on the ability of bacteria to reduce or avoid acti vation of PM Ns and the resultant release of lyso somal contents and oxygen-free radicals with micro bicidal properties [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive epidemiological studies indicate that serotype c is the most prevalent of the seven serotypes (a-g) in dental plaque [4][5][6][7][8][9][10][11][12][13]. Implantation experiments show also that serotype c has a much greater propensity than serotype a for colonising the oral cavity [14].…”
Section: Introductionmentioning
confidence: 99%